Manguju, Yudha Nugraha Pendekatan Teologi Kesehatan dan Psikoneuroimunologi Terhadap Kerentanan Bunuh Diri Masyarakat Toraja - Manguju, Yudha (STFT Jakarta, Indonesia, 2023)
The incident of suicide every year is a hot topic to talk about because it is one of the causes of the high mortality rate of mankind in the world. All circles of society now need to pay serious attention to this problem because the complexity of the problem in it consists of various aspects such as psychological, sociological, health. educational, cultural to theological. This paper aims to examine the vulnerability of suicide in Toraja society with the lens of health theology and psychoneuroimmunology. Using qualitative research methods with a literature study approach, this study shows that suicidal behavior occurs due to the inability to know and understand a healthy God in daily life which has an impact on instability of brain function and also an imbalance of the immune system in perpetrators who have suicidal ideation. From the theological and psychoneuroimmunological approaches it is found that religious beliefs and practices have an influence on the mental, social and physical health of the human being, in which the concept of a healthy God can generate healthy thoughts, feelings and behaviors. In this case, religious involvement has a significant correlation as a coping method for better mental health in minimizing all negative health behaviors, especially as a daily spiritual practice.